Violence here and there - Kloekner, Felipe (2003)
In all life and in all places on the planet, violence produces deep wounds in the current being, as well as in the past. A historical reading of our life also allows us to see to what extent this world is affected: numerous scars are still visible on a body with too recent wounds. Sometimes we have no remedy against it, sometimes it leaves visible amputations, others die from it. If history is marked by violence, today's world seems clumsy in resolving what we sometimes call "a misfortune."